Corporate Insurance with Safety Loadings: A Note - Lutz G. Arnold; Johannes Hartl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
In a paper in this journal, Schnabel and Roumi (1989) assert that if uninsured debt is risky, a levered firm takes a casualty insurance with a positive safety loading if, and only if, the amount of debt is sufficiently high. This note shows that, in marked contrast to this assertion, the correct conclusion from their model is that the firm generally takes insurance for low levels of risky debt, and it depends on the magnitude of the loading whether it also takes insurance for high levels of debt.
Keywords: 330; Unternehmensversicherung; Kapitalstruktur; Kreditrisiko; Theorie